The crash reel [videorecording (DVD)] - Walker, Lucy (Phase 4 Films, 2014)
The epic rivalry between half-pipe legends Kevin Pearce and Shaun White is documented in this exhilarating ride into the world of extreme snowboarding. With both practicing more and more breathtaking and dangerous tricks leading up to the Vancouver Winter Olympics, everything suddenly changes for Kevin when a horrific crash leaves him fighting for his life. When he recovers, all he wants to do is get on his snowboard again, even though medics and family fear it could kill him.